Comparison of the spatio-temporal distribution of the roughneck shrimp Rimapenaeus constrictus (Stimpson, 1874) (Crustacea, Penaeoidea) from monthly samples collected 20 years apart: Effects of a marine protected area in southeastern Brazil - Bernardes, Veronica P. [UNESP]; Sousa, Aline N. [UNESP]; Bernardo, Camila H. [UNESP]; Teixeira, Gustavo M.; Costa, Rogério C. [UNESP]; Mantelatto, Fernando L.; Fransozo, Adilson [UNESP] (Wiley, 2020)
This study was motivated by the data about a Rimapenaeus constrictus population from Ubatuba Bay, obtained in the 1990s, and by the establishment of a marine protected area (MPA) in the same region in 2008. We obtained comparable data about the distribution and abundance of this species collected 20 years apart, to evaluate the effectiveness of the MPA, for its preservation and possible changes in the populational profile. Biotic and abiotic data were obtained monthly, in September 1995–August 1996 (period 1 = 1ºP), and in September 2016–August 2017 (period 2 = 2ºP), from five transects within Ubatuba Bay. In total, 710 and 2,362 individuals were caught in the 1oP and 2oP, respectively. Despite this increase in abundance, aspects of the spatial distribution did not change substantially. The high abundance recorded at 5 m of depth was probably due to the creation of the MPA and to the accumulation of detritus at this depth. The high abundance seen in the transect sheltered from waves may be related to sediment heterogeneity, which was higher in this transect, and to the fact that this area is naturally protected from fisheries. In the 1ºP, the highest abundances were recorded in spring and summer, whereas in the 2ºP, they occurred in autumn and winter. This change may be explained by the entrance of the South Atlantic Central Water (SACW), which drives shrimps towards shallower areas. During the 2ºP, a fishing ban occurred in autumn (March 1st until May 31st), which is also when the SACW retreats and water temperature and salinity increase. These two factors combined may have been responsible for the increased shrimp abundance. In conclusion, both conservation practices (MPA and fishing ban) along with the existence of an area naturally protected from fisheries seem to have positively affected the population of R. constrictus, leading to an increase in abundance over the 20-year interval.
Keywords: bycatch; ecological distribution; fisheries; preservation; sedimentation; shrimps